Engineered Mott ground state in a LaTiO(3+δ)/LaNiO(3) heterostructure - Cao, Yanwei (Nat Commun, 2016)
In pursuit of creating cuprate-like electronic and orbital structures, artificial heterostructures based on LaNiO(3) have inspired a wealth of exciting experimental and theoretical results. However, to date there is a very limited experimental understanding of the electronic and orbital states emerging from interfacial charge transfer and their connections to the modified band structure at the interface. Towards this goal, we have synthesized a prototypical superlattice composed of a correlated metal LaNiO(3) and a doped Mott insulator LaTiO(3+δ), and investigated its electronic structure by resonant X-ray absorption spectroscopy combined with X-ray photoemission spectroscopy, electrical transport and theory calculations. The heterostructure exhibits interfacial charge transfer from Ti to Ni sites, giving rise to an insulating ground state with orbital polarization and e(g) orbital band splitting. Our findings demonstrate how the control over charge at the interface can be effectively used to create exotic electronic, orbital and spin states.